Agent of change needs a revolution - Abd Razak, Dzulkifli (2009)
PEOPLE walking along the cobbled streets of Paris towards the Unesco building last week where the World Conference on Higher Education was held were halted by a stream of at least 200 people on rollerskates and Rollerblades. The busy traffic along those congested streets was also disrupted. This stream of mobile people on the streets of Paris was rather symbolic of the "new dynamics" that mirrored the fourday Unesco conference, themed "The New Dynamics of Higher Education and Research for Societal Change and Development".